Effect of the Loading Rate on the Brittle Fracture of Terfenol-D Specimens in Magnetic Field: Strain Energy Density Approach - Colussi, M.; Berto, F.; Mori, K.; Narita, F. (Проблемы прочности, 2016)
The aim of the present study is to characterize the fracture behaviour of the giant magnetostrictive alloy commercially named Terfenol-D, both experimentally and numerically. Three-point bending tests have been carried out on single-edge precracked specimens and fracture loads have been measured at different loading rates,in the presence and absence of a magnetic field. In the recent years it has been shown that Strain Energy Density (SED), averaged in a finite control volume, can successfully predict brittle failures of cracked, U- and V-notched specimens made out of several materials. By performing coupled-field finite element analyses, the effect of the magnetic field and of the loading rate on Terfenol-D failures have been analyzed and the capability of SED criterion to capture these effects has been discussed.A relationship between the size of the SED’s control volume and the loading rate has been proposed and failures have then been predicted in terms of averaged SED. Экспериментально и путем расчета оценены характерные особенности разрушения инновационного магнитострикционного сплава Терфенол-Д. Плоские образцы из данного материала с исходной краевой трещиной испытывали на статический трехточечный изгиб с различными скоростями нагружения при наличии и отсутствии магнитного поля. Исследования показывают, что для описания характеристик разрушения образцов с трещиной либо надрезом V- или U-подобной формы достаточно перспективным является такой параметр, как плотность энергии деформации, осредненный по некоторому контрольному объему. С использованием конечноэлементного подхода проанализировано влияние магнитного поля и скорости нагружения на механизм разрушения сплава Терфенол-Д, а также возможность их учета с помощью критерия плотности энергии деформации. Предложена зависимость между размером контрольного объема осреднения и скоростью нагружения, а также выполнен прогноз разрушения исследуемого сплава в рамках указанного подхода. Експериментально і шляхом розрахунку оцінено характерні особливості руйнування іноваційного магнітострикційного сплаву Терфенол-Д. Плоскі зразки з даного матеріалу з вихідною крайовою тріщиною випробовували на статичний триточковий згин із різними швидкостями навантаження за наявності та відсутності магнітного поля. Дослідження показують, що для опису характеристик руйнування зразків із тріщиною або надрізом V- чи U-подібної форми досить перспективним є такий параметр, як щільність енергії деформації, осереднений по деякому контрольному об'єму. Із використанням скінченноелементного підходу проаналізовано вплив магнітного поля і швидкості навантаження на механізм руйнування сплаву Терфенол-Д та можливість їх урахування за допомогою критерію щільності енергії деформації. Запропоновано залежність між розміром контрольного об'єму осереднення і швидкістю навантаження та виконано прогноз руйнування досліджуваного сплаву в рамках указаного підходу.